A Novel Sleep Positioning Device Reduces Gastroesophageal Reflux: A Randomized Controlled Trial. Issue 8 (September 2015) - Person, Erik; Rife, Christopher; Freeman, Janice; Clark, Aaron; Castell, Donald O.
Abstract : Goal: We hypothesized that sleeping left-side down with the head/torso elevated reduces recumbent gastroesophageal reflux (GER). Background: Previous studies show that sleeping with head of bed elevated or on wedge reduces GER and lying left-side down reduces GER versus right-side down and supine. No prior studies have evaluated the potential compounding effects of lying in an inclined position combined with lateral positioning on GER. Study: We evaluated a sleep-positioning device (SPD) consisting of an inclined base and body pillow that maintains lateral position while elevating the head/torso. This was a single institution, randomized controlled trial involving 20 healthy volunteers receiving 4 six-hour impedance-pH tests. After placement of reflux probe, subjects returned home, ate standardized meal, and lay down in randomly assigned positions: SPD right-side down (SPD-R), SPD left-side down (SPD-L), standard wedge any position (W), or flat any position (F). A wireless accelerometer documented position during each study. Number of reflux episodes (RE) and esophageal acid exposure (EAE) were calculated over 6 hours. Results: Significantly less EAE occurred during sleeping SPD-L versus sleeping W, SPD-R, and F. The most EAE occurred during sleeping SPD-R despite use of the positioning device. RE were significantly less SPD-L than SPD-R. Patients sleeping SPD-L and SPD-R spent the majority of first 2 hours and greater than half of 6 hours in assigned position. Patients sleeping W and F averaged more time supine than right or left. Conclusions: The sleep positioning device maintains recumbent position effectively. Lying left-side down, it reduces recumbent esophageal acid exposure.